Family climate and its relation to positive thinking among first year secondary students - rahmani, djamel (Journal of Social Sciences and Humanities, 2020)
This study aimed to identify the Relationship between the family climate and positive thinking among secondary school students in the Wilayat of M'sila. Using the statistical package software (spss), we have reached the following results: -There is a correlation between the family climate and positive thinking among the first year secondary school students. -There are statistically significant differences in the level of the family climate in the pupils of the first year secondary, depending on the variables of the study (sex and specialization). -There are statistically significant differences in the level of positive thinking in the first year secondary school students, depending on the study variables (sex and specialization).